Women Integration into Agricultural Development Projects: Challenges and Opportunities - M O Akinola; L O Aja; Y L Amapu (Journal of Agricultural Extension, 2007)
The research work was designed to appraise the extent of women's involvement in the ISFM/IAP project in Unguwar Madaki (U/M) and Danja villages, both in Danja Local Government Area of Katsina State. The specific objectives were to examine the social characteristics of the women farmers, the challenges and opportunities of their involvementin the project andbenefits ofparticipation. Sixty (60) women farmers were purposively. selected for interview in the study areas, using structured interview schedule. The information collected was analyzed using descriptive statistics, gross farm income. Results from the analysis showed that majority of the womenin U/M were relatively young and uneducated, but generally belong to one social group or another. The reverse was the case with women farmers in Danja town who were averagely educated but socially secluded. The gross margin analysis revealed that the participating women made a profit of N232, 411.55/ha while the non-participating women made a profit of N94,375.81/ha. The major challenges facing the women farmers in U/Mincluded illiteracy, lack of basic infrastructure and unfavourable market conditions. In Danja, however, the purdah system and inadequate extension contacts were the majorproblems. Provision ofadequate ruralinfrastructure like schools, feeder roads andmarketingoutlets for the farmersproduce wouldhelp improve andsustain the gains fromparticipatingin thisproject.